Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1885)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Casus Conscientiae, his praesertim temporibus accommodati (Typis Alfredi Vromant, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Casus Conscientiae, his praesertim temporibus accommodati (Typis Alfredi Vromant, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Letters de M. Olier (Librairie Victor Lecoffre, 1885)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Um Bispo Segundo Deus ou Memorias Para a vida de D. Manuel De Aguiar (Typ de Reis Leitao, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

As Chammas Do Amor De Jesus - Abbade D. Pinnard (Typ. da Palavra, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Religion

As Chammas Do Amor De Jesus - Abbade D. Pinnard (Typ. da Palavra, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Vidas de Los Hermanos - Alvarez, Paulin (1885)
Keywords: 1.Conservation 保護; 2.Damage

A religião em face da sciencia: lições sobre o accordo entre os dados da revelação biblica e as theorias scientificas modernas - Arduin, Alexis; Almeida Netto, Antonio Maria d'; Almeida, Jose Maria d' (Livraria Académica, Editora de José Maria d'Almeida, 1885)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion; Religión y ciencia

A religião em face da sciencia: lições sobre o accordo entre os dados da revelação biblica e as theorias scientificas modernas - Arduin, Alexis; Almeida Netto, Antonio Maria d'; Almeida, Jose Maria d' (Livraria Académica, Editora de José Maria d'Almeida, 1885)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion; Religión y ciencia

Meditacoes Sacerdotaes - Chaignon, R. P. (Typ. de A. J. da Silva Teixeira, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Meditacoes Sacerdotaes - Chaignon, R. P. (Typ. de A. J. da Silva Teixeira, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cursus Scripturae Sacrae, Historica et Critica Introductio - Cornely, Rudolphus (Sumptibus P. Lethielleux, Editoris, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Everyday life in China or Scenes along river and road - Dukes, Edwin Joshua (The Religious Tract Society, 1885)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Bibliotheca - F. Lucii Ferraris (Ex Typographia Polyglotta, 1885)
Stamp of St. Joseph Seminary
Keywords: Good

Meditaçôes sacerdotaes ou O Padre santificado pela oraçâo - Francisco Luís de Seabra (Ernesto Chardron, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy; Religion

Les Peres Apostoliques et Leur Epoque - Freppel, Mgr (Bray et Retaux, Libraires-Editeurs, 1885)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm

Hygiene social applicada á nação portugueza: conferencias feitas no Porto. 1. sér - Jorge, Ricardo (Imprensa Civilizacao, 1885)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Portugal; Public Health; Public health; Santé publique; public health

Nouveau Commentaire Litteral, Critique et Theologique, avec rapport aux testes primitifs, sur tous les lives des divines ecritures. - M. Le Docteur J. F. D'Allioli (Chez Louis Vives, 1885)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm (Only Cover); 2.Damage

O escholiaste portuguez ou, Subsidios litterarios, grammaticaes, philologicos e rhetoricos compilados dos melhores auctores e divididos em tres partes accommodadas ao estudo elementar e complementar da lingua portugueza - Netto, Antonio Maria d'Almeida (Livraria Ferreira, 1885)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Portugais (Langue); Portuguese language; Portuguese language Grammar; Portuguese language Grammar 1870-; Since 1870; languages

Lettres de M. Olier - Oliver, M. (Librairie Victor Lecoffre, 1885)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Elements De Botanique - P. Duchartre (Librairie J.- B. Bailliere et Fils, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Teaching

Les Petits Bollandistes- Vies Des Saints - Paul Guerin (Bloud et Barral, 1885)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; Religion

O Culto Catholico Com Solemnidade e Sem Ministros Sagrados - Pimentel, D. Joao (Typ. Virgem Immaculada, 1885)
Keywords: 1.Conservation 保護; 2.Damage

Sanctorum Patrum Opouscula Selecta de S. Marino - Severi Sulpicii (Typis Wagnerianis, 1885)
Keywords: 1.Conservation 保護; 2.Damage

古史参 箴卷三 - 沈, 則寬; 南, 志恆; 應, 儒望 (慈母堂, 1885)
Keywords: Catholic Church--China